Benchmarking life expectancy and cancer mortality: global comparison with cardiovascular disease 1981-2010. (21st June 2017) - Cao, Bochen; Bray, Freddie; Beltrán-Sánchez, Hiram; Ginsburg, Ophira; Soneji, Samir; Soerjomataram, Isabelle
Abstract : Objective To quantify the impact of cancer (all cancers combined and major sites) compared with cardiovascular disease (CVD) on longevity worldwide during 1981-2010. Design Retrospective demographic analysis using aggregated data. Setting National civil registration systems in member states of the World Health Organization. Participants 52 populations with moderate to high quality data on cause specific mortality. Main outcome measures Disease specific contributions to changes in life expectancy in ages 40-84 (LE40-84 ) over time in populations grouped by two levels of Human Development Index (HDI) values. Results Declining CVD mortality rates during 1981-2010 contributed to, on average, over half of the gains in LE40-84 ; the corresponding gains were 2.3 (men) and 1.7 (women) years, and 0.5 (men) and 0.8 (women) years in very high and medium and high HDI populations, respectively. Declines in cancer mortality rates contributed to, on average, 20% of the gains in LE40-84, or 0.8 (men) and 0.5 (women) years in very high HDI populations, and to over 10% or 0.2 years (both sexes) in medium and high HDI populations. Declining lung cancer mortality rates brought about the largest LE40-84 gain in men in very high HDI populations (up to 0.7 years in the Netherlands), whereas in medium and high HDI populations its contribution was smaller yet still positive. Among women, declines in breast cancer mortality rates were largely responsible for the improvement in longevity, particularly among very high HDI populations (up to 0.3 years in the United Kingdom). In contrast, losses in LE40-84 were observed in many medium and high HDI populations as a result of increasing breast cancer mortality rates. Conclusions The control of CVD has led to substantial gains in LE40-84 worldwide. The inequality in improvement in longevity attributed to declining cancer mortality rates reflects inequities in implementation of cancer control, particularly in less resourced populations and in women. Global actions are needed to revitalize efforts for cancer control, with a specific focus on less resourced countries.